Reduction of paediatric in-patient cardiac arrest and death with a medical emergency team: preliminary results. Issue 11 (21st October 2005) - Tibballs, J; Kinney, S; Duke, T; Oakley, E; Hennessy, M
Abstract : Aims: To determine the impact of a paediatric medical emergency team (MET) on cardiac arrest, mortality, and unplanned admission to intensive care in a paediatric tertiary care hospital. Methods: Comparison of the retrospective incidence of cardiac arrest and death during 41 months before introduction of a MET service with the prospective incidence of these events during 12 months after its introduction. Comparison of transgression of MET call criteria in patients who arrested and died before and after introduction of MET. Results: Cardiac arrest decreased from 20 among 104 780 admissions (0.19/1000) to 4 among 35 892 admissions (0.11/1000) (risk ratio 1.71, 95% CI 0.59 to 5.01), while death decreased from 13 (0.12/1000) to 2 (0.06/1000) during these periods (risk ratio 2.22, 95% CI 0.50 to 9.87). Unplanned admissions to intensive care increased from 20 (SD 6) to 24 (SD 9) per month. The incidence of transgression of MET call criteria in patients who arrested decreased from 17 to 0 (risk difference 0.16/1000, 95% CI 0.09 to 0.24), and in those who died, decreased from 12 to 0 (risk difference 0.11/1000, 95% CI 0.05 to 0.18) after introduction of MET. Conclusions: Introduction of a medical emergency team service was coincident with a reduction of cardiac arrest and mortality and a slight increase in admissions to intensive care.